Natural variation in rice starch synthase iia affects enzyme and starch properties - Umemoto, T.; Aoki, N.; Lin, H.; Nakamura, Y.; Inouchi, N.; Sato, Y.; Yano, M.; Yano, M.; Maruyama ,S.
The natural variation in starch synthase IIa (SSIIa)of rice (Oryza sativa L.)was characterised using near-isogenic lines (NILs). SSIIa is a candidate for the alk gene regulating the alkali disintegration of rice grains, since both genes are genetically mapped at the same position on chromosome 6 and related to starch properties. In this study, we report that the alkali-susceptible cultivar Nipponbare lacked SSIIa activity in endosperm. However, the activity was detected with NILs having the alk allele of alkali-tolerant Kasalath. SSIIa protein was present even in Nipponbare endosperm, but it was not associated with starch granules at the milky stage of endosperm. Three single-nucleotide polymorphisms (SNPs)predicting amino acid substitutions existed between the cDNA sequences of SSIIa of Nipponbare and Kasalath were genotyped with 65 rice cultivars and four wild relatives of cultivated rice. The results obtained explain the potential importance of two of the amino acid residues for starch association of rice SSIIa. An analysis of the chain-length distribution of ß-limit dextrin of amylopectin showed that without SSIIa activity, the relative number of A-chains (the short chains without branches)increased and that of B1-chains (the short chains with branches)decreased. This suggests that, given the SSIIa defect, short A-chains could not reach a sufficient length for branching enzymes to act on them to produce B1-chains
Keywords: ALK; ALKALI DISINTEGRATION; AMYLOPECTIN; RICE; STARCH SYNTHASE